Studies on the orientation of radiators For high‐gain line‐fed array antenna. Issue 6 (27th March 2013) - Kahar, Manisha; Ray, Arup; Sarkar, P. P
Abstract Two antenna systems, each consisting of two microstrip line‐fed monopole antenna elements, differing in element geometry have been designed, investigated, and optimized for favorable antenna characteristics including the properties of ultra wide band, omnidirectional radiation characteristics, and high gain. Interestingly most parameters of credit were alike in the two designs except for the antenna gain which was remarkable high in the second design compared to the first one. The cause of difference has also been considered. © 2013 Wiley Periodicals, Inc. Microwave Opt Technol Lett 55:1348–1351, 2013; View this article online at wileyonlinelibrary.com. DOI 10.1002/mop.27567